The current challenges of International laws for animal welfare: Bridging the gaps through innovative approaches. (International Journal of Food and Nutritional Sciences, 2023)
The condition of the animals across the world is very pathetic. They suffer on daily basis either because of human’s oppressive treatments on them or because of human needs and greed. This major social issue has not been solved yet because there is no international agreement that provides protection and welfare of animals. Lack of International law is the main reason behind the cruel treatment of animals all over the world. Different countries have different set of laws for providing protection to animals. Few developed countries have strong laws while in some developing countries there is complete absence of laws, or the laws have no standards at all. Interestingly, even countries that has animal welfare standards in place, the degree of legal protection may be different as per situations. This paper would like to highlight the current challenges faced by the prevailing guidelines in international law that has tried to address animal welfare partiality, but they are not able to give effective protection which is important to raise the status of animals in our society. This research paper would like to support the eminent animal law scholar’s David Favre’s idea to revive the proposal of adopting the international convention for the Protection of Animals (ICPA) is important because the main objective of the treaty is to focus on the animal welfare issues and to receive international recognition and protection by setting the general guidelines and polices regarding the treatment and use of animals. There might be some challenges in passing the treaty by all the countries. However, the ICPA can come into force by applying smart strategies. In this paper the researcher would like to recommend the urgent need of an international treaty for animal welfare to ensure uniform legal protection towards domestic animals and stray animals by following doctrinal research method.